Factors affecting the intention and behavior to adopt blockchain technology in Ho Chi Minh City, Viet Nam - My, Vo Thi Tra (Edelweiss Applied Science and Technology, 2025)
This study investigates the factors influencing the intention and behavior toward the adoption of blockchain technology in Ho Chi Minh City, Vietnam, in the context of its growing importance in digital transformation and business model innovation. Based on survey data collected from 84 respondents and analyzed using the PLS-SEM approach, the research integrates two well-established theoretical models (TAM) and (UTAUT2) to provide a comprehensive evaluation of the determinants affecting blockchain adoption. The results indicate that effort expectancy (EE), facilitating conditions (FC), social influence (SI), trust in blockchain (BB), and blockchain transparency (BT) all have a positive impact on the intention to use blockchain, with effort expectancy (EE) emerging as the most influential factor. Furthermore, behavioral intention (BI) is found to significantly influence actual usage behavior (AU), whereas performance expectancy (PE) does not show statistically significant effects. This investigation represents one of the pioneering efforts to explore blockchain adoption in Vietnam and contributes to the development of blockchain-based enterprises through a conceptual framework for technology acceptance, particularly regarding individual employee behavior within organizations.